2015
DOI: 10.1159/000371700
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Food Allergies

Abstract: Gastrointestinal food allergies present during early childhood with a diverse range of symptoms. Cow's milk, soy and wheat are the three most common gastrointestinal food allergens. Several clinical syndromes have been described, including food protein-induced enteropathy, proctocolitis and enterocolitis. In contrast with immediate, IgE-mediated food allergies, the onset of gastrointestinal symptoms is delayed for at least 1-2 hours after ingestion in non-IgE-mediated allergic disorders. The pathophysiology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 68 publications
(66 reference statements)
1
21
1
5
Order By: Relevance
“…Nevertheless, from the published data, it is thought that children with food protein–induced enteropathy present with gastrointestinal symptoms in early infancy. Data on cow's milk– and soya‐related enteropathy indicate presentation within the first 2 years of life, and although current data indicate that the majority outgrow this allergy by 24‐36 months of age, a study from Kokkonen et al does indicate that this non‐IgE‐mediated allergy may persist into the early school years.…”
Section: The Natural Course Of Non‐ige‐mediated Gastrointestinal Allementioning
confidence: 62%
See 1 more Smart Citation
“…Nevertheless, from the published data, it is thought that children with food protein–induced enteropathy present with gastrointestinal symptoms in early infancy. Data on cow's milk– and soya‐related enteropathy indicate presentation within the first 2 years of life, and although current data indicate that the majority outgrow this allergy by 24‐36 months of age, a study from Kokkonen et al does indicate that this non‐IgE‐mediated allergy may persist into the early school years.…”
Section: The Natural Course Of Non‐ige‐mediated Gastrointestinal Allementioning
confidence: 62%
“…Using the European Academy for Allergy and Clinical Immunology (EAACI) nomenclature, this allergic disorder encompasses different gastrointestinal allergies varying in presentation and includes food protein-induced allergic proctocolitis, food protein-induced enterocolitis syndrome (FPIES), food protein-induced enteropathy, allergic dysmotility disorders [gastro-oesophageal reflux disorder (GORD) and constipation], eosinophilic gastrointestinal disorders (EGID), including eosinophilic oesophagitis (EoE) and non-IgE-mediated AD (Figure 1). [15][16][17][18] According to the nomenclature of the National Institute for Allergy and Infectious Disease, EoE is classified as a mixed IgE and non-IgEmediated allergy; however, this was published prior to the recent article by Simon et al, 19 proposing EoE as a non-IgE-mediated allergic condition. For the purpose of this publication, EoE will be therefore discussed as a non-IgE-mediated condition, as per EAACI nomenclature.…”
Section: Defining Non -I G E-med Iated Food Allerg Ie Smentioning
confidence: 99%
“…Faulty feeding techniques (i.e., underfeeding, overfeeding, and/or swallowing air) may also contribute to colic development (135). Food allergens may be relevant in a subset of patients with severe colic (132) and those with atopic dermatitis. Systematic reviews confirmed the benefit of hypoallergenic hydrolyzed or soy formula as well as low-allergenic maternal diet in exclusively breastfed colicky infants (17,18,20,132,(136)(137)(138)(139)(140)(141)(142)(143).…”
Section: Colicmentioning
confidence: 99%
“…Food allergens may be relevant in a subset of patients with severe colic (132) and those with atopic dermatitis. Systematic reviews confirmed the benefit of hypoallergenic hydrolyzed or soy formula as well as low-allergenic maternal diet in exclusively breastfed colicky infants (17,18,20,132,(136)(137)(138)(139)(140)(141)(142)(143). However, these studies have methodological limitations and the fact that colic is a transient disorder resolving within few weeks, renders investigations of the effect of restrictive diet particularly difficult (144).…”
Section: Colicmentioning
confidence: 99%
See 1 more Smart Citation